Behavior of detached simulation plasma by suddenly changed particle flux in GAMMA 10/PDX - Masayuki Yoshikawa; Junko Kohagura; Naomichi Ezumi; Tsuyoshi Kariya; Ryutaro Minami; Tomoharu Numakura; Mafumi Hirata; Satoshi Togo; Mizuki Sakamoto; Yousuke Nakashima; Yoriko Shima; Takuma Okamoto; et al. (AIP Advances, 2024)
Plasma detachment is one of the most significant factors affecting nuclear fusion reactors. GAMMA 10/PDX has a divertor simulation experimental module (D-module) for detached plasma studies in the end region. To investigate the effect of suddenly changing the higher-density particle flux into the detached plasma condition, similar to edge-localized mode simulations, we performed supersonic molecular beam injection (SMBI) and electron cyclotron heating (ECH) experiments to produce a higher-density and higher-temperature core plasma and introduced it to the divertor simulation plasma in the D-module. With the application of ECH, the detached plasma moved to the attached condition. Moreover, with the injection of SMBI into the ECH-injected plasma, the attached plasma moved to a detached condition. This study revealed the effect of sudden changes in the particle flux on detached simulation plasma for the first time.